2009
DOI: 10.1088/0004-637x/706/1/l12
|View full text |Cite
|
Sign up to set email alerts
|

Farley-Buneman Instability in the Solar Chromosphere

Abstract: The Farley-Buneman instability is studied in the partially ionized plasma of the solar chromosphere taking into account the finite magnetization of the ions and Coulomb collisions. We obtain the threshold value for the relative velocity between ions and electrons necessary for the instability to develop. It is shown that Coulomb collisions play a destabilizing role in the sense that they enable the instability even in the regions where the ion magnetization is greater than unity. By applying these results to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…The magnitude of the nonlinear coefficients depend on the relative concentration, mass and collision frequencies of ion species as shown in Eq. (36). The situations with several ion species exist in the E-region of the Earth's ionosphere and solar chromosphere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the nonlinear coefficients depend on the relative concentration, mass and collision frequencies of ion species as shown in Eq. (36). The situations with several ion species exist in the E-region of the Earth's ionosphere and solar chromosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the wave steepening nonlinear term may result in wave breaking and forming strongly nonlinear singular solutions. It is worth noting that the FB waves in multispecies plasmas have recently been studied in application to the solar physics problems [33][34][35][36]. It has been suggested that FB instability plays an important role in the heating of solar chromosphere [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way is to find an instability with threshold which is much less than the threshold of the ion-acoustic instability (see e.g. Galeev et al, 1972;Duijveman et al, 1981;Somov et al, 1987;Voitenko and Goossens, 2002;Kryshtal and Gerasimenko, 2004;Fontenla et al, 2008;Gogoberidze et al, 2009;Kryshtal et al, 2012, for details). Under some conditions these instabilities can transform into weak and then later into saturated turbulence.…”
Section: Physical Approximations and Basic Formulasmentioning
confidence: 99%
“…Later, FBI was investigated further in order to obtain the revised semi-empirical models of the solar chromosphere, which vary from the quiet solar atmosphere Vernazza-Avrett-Loeser (VAL) and more recent FontenlaAvrett-Loeser (FAL) models (see Fontenla et al, 2008Fontenla et al, , 1993Vernazza et al, 1981). The generation mechanism of smallscale density irregularities in the partially ionized plasma of the solar chromosphere by FBI was reported by Gogoberidze et al (2009). These small-scale irregularities can be used for remote diagnostics of strong cross-field currents in the solar chromosphere.…”
Section: Introductionmentioning
confidence: 99%